EFEITOS DO HUMAN FOOTPRINT, ESPÉCIES INVASORAS E DE DOENÇAS EMERGENTES EM PADRÕES DE DIVERSIDADE DE ANFÍBIOS NEOTROPICAIS - Philip Teles Soares (2023)
Amphibians are one of the main groups of globally threatened vertebrates, suffering constant declines. Several threats are responsible for these declines, such as climate change, habitat fragmentation and conversion of natural areas, as well as pathogens and invasive species. Amphibians are affected by these threats due to aspects of their life history, such as dependence on the aquatic environment, their physiology and sensitivity to temperature variations. Despite the knowledge about these impacts, it is still uncertain how they are acting together for the decline of amphibians and how they affect the different facets of diversity (taxonomic, functional and phylogenetic) in the Neotropics. Thus, this thesis aimed (Chapter 1) to investigate how global climate change in conjunction with invasive species (in this case Lithobates catesbeianus - Lc) (Shaw, 1802) (Anura: Ranidae) and the chytrid fungus (Batrachochytrium dendrobatidis - Bd) (Berger, 1998) (Fungi, Chytridiomycota, Rhizophydiales), which causes chytridiomycosis, affect the distribution of anurans in the Neotropics. In addition, (Chapter 2) we seek to understand how anthropic threats affect the different facets of amphibian diversity in the region neotropical and how they relate to the distribution of Bd and Lc. In the first chapter we generate potential distribution models for Bd and Lc and for 46 Neotropical anuran species for the current and future (2100) scenarios. In addition, we tested the overlapping of climatic niches and also the generated suitability maps and compared them. The distribution of native anuran species tends to decrease in the coming years due to climate change, while that of the invasive bullfrog species and Batrachochytrium dendrobatidis (Bd) will increase in the coming years, overlapping with native species. Thus, there will be a synergistic effect of these threats, further accentuating their decline. In the second chapter, we tested how the variables of land use and human population density (used to create the Human Footprint Index - HF) affect different facets 4 of diversity and how this diversity is related to the potential distribution of Bd and Lc. For this, we collected species information from IUCN data and from there we calculated the richness (taxonomic diversity), functional and phylogenetic diversity of species. We also collected information on anthropogenic variables from databases and generated current distribution models for Bd and Lc (same models as in Chapter 1). We found that facets of diversity are generally negatively related to anthropic variables in most of the Neotropical region. Furthermore, most of the diversity is located in regions where Bd is present. Added to this, both Bd and Lc tend to occur in regions where land use variables such as monocultures and pastures are greater. Thus, in addition to the fragmentation of natural environments of Neotropical anurans, we have the negative influence of invasive species. These threats can lead to the extinction not only of species, but to the loss of functional attributes and entire lineages. Thus, it is necessary to consider these threats and develop policies and conservation plans that take into account their action together, thus avoiding the homogenization of diversity and the maintenance of areas of occurrence of Neotropical anuran species.